In neonates S100A8/S100A9 alarmins prevent the expansion of a specific inflammatory monocyte population promoting septic shock. Issue 3 (19th December 2016) - Heinemann, Anna S.; Pirr, Sabine; Fehlhaber, Beate; Mellinger, Lara; Burgmann, Johanna; Busse, Mandy; Ginzel, Marco; Friesenhagen, Judith; von Köckritz-Blickwede, Maren; Ulas, Thomas; von Kaisenberg, Constantin S.; Roth, Johannes; et al.
ABSTRACT: The high susceptibility of newborn infants to sepsis is as cribed to animmaturity of the neonatal immune system, but the molecular mechanisms remain unclear. Newborn monocytes massively release the alarmins S100A8/S100A9. In adults, these are major regulators of immunosuppressive myeloid‐derived suppressor cells (MDSCs). We investigated whether S100A8/S100A9 cause an expansion of monocytic MDSCs (Mo‐MDSCs) in neonates, thereby contributing to an immunocompromised state. Mo‐MDSCs have been assigned to CD14 + /human leukocyte antigen (HLA)‐DR −/low /CD33 + monocytes in humans and to CD11b + /Gr‐1 int /Ly6G − /Ly6C hi cells in mice. We found monocytes with these phenotypes significantly expanded in their respective newborns. Functionally, however, they did not prove immunosuppressive but rather responded inflammatorily to microbial stimulation. Their expansion did not correlate with high S100A8/S100A9 levels in cord blood. Murine studies revealed an excessive expansion of CD11b + /Gr‐1 int /Ly6G − /Ly6C hi monocytes in S100A9 −/− neonates compared to wild‐type neonates. This strong baseline expansion was associated with hyperinflammatory responses during endotoxemia and fatal septic courses. Treating S100A9 −/− neonates directly after birth with S100A8/S100A9 alarmins prevented excessive expansion of this inflammatory monocyte population and death from septic shock. Our data suggest that a specific population of inflammatory monocytes promotes fatal courses of sepsis in neonates if its expansion is not regulated by S100A8/S100A9 alarmins.—Heinemann, A. S., Pirr, S., Fehlhaber, B., Mellinger, L., Burgmann, J., Busse, M., Ginzel, M., Friesenhagen, J., von Köckritz‐Blickwede, M., Ulas, T., von Kaisenberg, C. S., Roth, J., Vogl, T., Viemann, D. In neonates S100A8/S100A9 alarmins prevent the expansion of a specific inflammatory monocyte population promoting septic shock. FASEB J. 31, 1153–1164 (2017). www.fasebj.org